2004
DOI: 10.1007/s10654-004-2253-z
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and serum folate in childbearing age women

Abstract: Lower folate level may be one mechanism linking higher maternal BMI and increased risk of NTDs in the offspring. If corroborated in future studies, findings from this study suggest a need for a higher dose of folate supplement in heavier childbearing age women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(131 citation statements)
references
References 31 publications
9
118
0
4
Order By: Relevance
“…Therefore, it is hardly surprising that the prevalence of neonatal neural tube defects is raised in obesity, given the likelihood of folate deficiency. 87,88 Management of obesity in pregnancy and between pregnancies…”
Section: Lipid Turnovermentioning
confidence: 99%
“…Therefore, it is hardly surprising that the prevalence of neonatal neural tube defects is raised in obesity, given the likelihood of folate deficiency. 87,88 Management of obesity in pregnancy and between pregnancies…”
Section: Lipid Turnovermentioning
confidence: 99%
“…However, research on the relationship between obesity and folate levels is only now evolving and includes only a handful of studies to date. Mojtabai (2004) found that increased body mass index (BMI) in US women of childbearing age was associated with lower serum folate levels both before and after folic acid fortification. Tungtrongchitr et al (2003), reported that obese Thai subjects have lower serum folate than normal weight subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have observed a differential association between obesity and serum and red-blood-cell (RBC) folate concentrations in men, non-pregnant women of childbearing age and postmenopausal women (1)(2)(3)(4)(5) . Specifically, serum folate was found to be negatively associated, while RBC folate was positively associated, with BMI among non-pregnant adults (1)(2)(3)(4)(5) . The mechanisms for this differential association of obesity with serum and RBC folate concentrations are not clearly understood.…”
mentioning
confidence: 99%